Karthik delivers - Chari, Sheela (Amulet Books, 2022)
One summer during the Financial Crisis, fourteen-year-old Karthik Raghavan makes deliveries for his father's ailing Indian grocery, but he is secretly cast in a play about the young Leonard Bernstein. Includes author's note.